The acute effect of mental fatigue on badminton performance in elite players - Kosack, M. H.; Staiano, W.; Folino, R.; Hansen, M. B.; Lønbro, S. (International Journal of Sports Physiology and Performance, 2020)
Purpose: Several studies have examined the effect of MF on sport performance, but no studies have been conducted on badminton performance. The purpose of the present study was to examine the acute effect of mental fatigue (MF) on badminton performance in elite players. Methods: In total, 19 elite Danish badminton players completed 2 test days in randomized order, separated by 48 h. On day 1, to elicit MF, a 60-min incongruent Stroop task was performed. On day 2, 60 min of an emotionally neutral documentary was used for the control condition. After either condition, subjects performed a badminton-specific test (BST) where performance time was measured, as well as countermovement-jump height, heart rate, rating of perceived exertion, and lactate. Psychological questionnaires were answered under both conditions. Results: Subjects were significantly more mentally fatigued (P=.002) after the Stroop intervention than in the control. No differences between conditions were detected in the BST (control 32.43 [1.96] vs MF 32.43 [2.36] s; P=.99, Student t test). In addition, no effect of condition (P=.64), time (P=.14), or condition ×time (P=.87) was found (2-way analysis of variance). Furthermore, no differences in heart rate, countermovement jump, or rating of perceived exertion were observed between conditions. Lactate showed no effect of condition (P=.46). Conclusion: Despite being more mentally fatigued after the Stroop test than in the control condition, performance was not negatively affected during a BST. In addition, no differences in physiological measures were observed.